Potential of the chemical dinotefuran in the control of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged female ticks - Oliveira, Patricia Rosa de [UNESP]; Pizano, Marcos Aparecido [UNESP]; Remedio, Rafael Neodini [UNESP]; Bechara, Gervasio Henrique [UNESP]; Magalhaes de Abreu, Rusleyd Maria; Camargo Mathias, Maria Izabel [UNESP] (Elsevier B.V., 2015)
Ticks are vectors of several pathogens to vertebrates, including the human being. They produce lesions on the hosts during the blood feeding and great economic losses. Several chemical acaricides have been used in an attempt to control tick infestations; however these substances are harmful to both the human being and non-target organisms, and to the environment. Therefore, there is a need to fight these ecto-parasites through less harmful methods, less aggressive to the environment, non-target organisms and to the human health. The present study examined the efficacy of dinotefuran on the susceptibility of Rhipicephalus sanguineus semi-engorged females exposed to different concentrations of the product. Its lethal concentration of 50% (LC50) at 95% confidence interval was determined. The ticks were immersed in Petri dishes containing different concentrations of dinotefuran or distilled water for 5 minutes and then dried and maintained in an incubator for 7 days. The results showed the daily number of dead R. sanguineus semi-engorged females after being treated with different concentrations of dinotefuran. The mortality data in bioassay 2 were subjected to Probit analysis, where a LC50 of 10,182.253 ppm (8725.987-13,440.084) and 95% confidence interval were estimated. The susceptibility of R. sanguineus semi-engorged females to dinotefuran in higher concentrations of the acaricide was demonstrated, indicating that its effect is probably dose-dependent. In addition, the action of dinotefuran was slow and gradual, interfering in the development and growth of the individuals throughout the observation period (7 days). (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Dinotefuran; Rhipicephalus sanguineus; Tick; Acaricide; Neonicotinoids